5x-12+15x-7+9-2x=-15

Simple and best practice solution for 5x-12+15x-7+9-2x=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-12+15x-7+9-2x=-15 equation:


Simplifying
5x + -12 + 15x + -7 + 9 + -2x = -15

Reorder the terms:
-12 + -7 + 9 + 5x + 15x + -2x = -15

Combine like terms: -12 + -7 = -19
-19 + 9 + 5x + 15x + -2x = -15

Combine like terms: -19 + 9 = -10
-10 + 5x + 15x + -2x = -15

Combine like terms: 5x + 15x = 20x
-10 + 20x + -2x = -15

Combine like terms: 20x + -2x = 18x
-10 + 18x = -15

Solving
-10 + 18x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 18x = -15 + 10

Combine like terms: -10 + 10 = 0
0 + 18x = -15 + 10
18x = -15 + 10

Combine like terms: -15 + 10 = -5
18x = -5

Divide each side by '18'.
x = -0.2777777778

Simplifying
x = -0.2777777778

See similar equations:

| 12-7x-10=x-8x+2 | | t^2-2=0 | | 3a+4(2a-17)=-13 | | 9.99x+.25=113.74 | | 32x-21+-5x+30= | | 1=6p+6-p | | -(3x+2)-(x-1)=(2x-2)-(2x+4) | | 10-3x-1=7+3x+2 | | 1+5(x-8)=2-1(x+5) | | -2=v-6 | | 2x-8=128 | | M=8+3*3 | | 10+4x=46 | | 16=5z-9 | | 9x^2-x+32=0 | | p-65.7=24.81 | | M=8+3*1 | | 1/2+7y=-3 | | 1+2x=2x-5 | | 2+20t-5t^2=0 | | M=8+3*-1 | | 55.00+8.50x= | | 2(4x+4)=-8 | | -d+3=2d | | 6p-6p+18-13-5p= | | 3c+5d=7d-6cford | | Y-5.8=2.3 | | V+2.4=7.95 | | -8x^2-80x-168=0 | | 2745x-1800=45(61x-40) | | V+2.4=7.25 | | 9-6(4u-6)=u+15 |

Equations solver categories